2012
DOI: 10.1111/pai.12020
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing multiple drug hypersensitivity in children

Abstract: MDH can occur in children, even to drugs other than antibiotics. It is crucial to evaluate children with histories of MDH using both in vivo and in vitro allergologic tests, including challenges. In fact, such approach allows the physician to confirm the diagnosis of MDH in a small percentage of children with histories of MDH, as well as to rule it out in the great majority of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 34 publications
1
54
0
2
Order By: Relevance
“…[4,8] Similar to our observations, others also noted multiple drug allergy to be rare in children; but Atanaskovic et al in their study on drug reaction in pediatric population documented that 2.5% of those with suspected drug allergy were allegic to multiple drugs. [9] The reaction patterns observed were comparable to existing data on multiple drug allergy. [1] Unlike described in literature, most of the patients with multiple drug allergy syndrome in our study (90%) showed similar pattern of reaction irrespective of the culprit drug.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…[4,8] Similar to our observations, others also noted multiple drug allergy to be rare in children; but Atanaskovic et al in their study on drug reaction in pediatric population documented that 2.5% of those with suspected drug allergy were allegic to multiple drugs. [9] The reaction patterns observed were comparable to existing data on multiple drug allergy. [1] Unlike described in literature, most of the patients with multiple drug allergy syndrome in our study (90%) showed similar pattern of reaction irrespective of the culprit drug.…”
Section: Discussionsupporting
confidence: 73%
“…[2] Unlike our study, some other studies found antiepileptics to be one of the offenders. [9,10] Nine out of ten patients with multiple drug allergy syndrome in our study group showed allergic reaction to one or more NSAIDs and in six of them the first episode of drug allergy was precipitated by a NSAID.…”
Section: Discussionmentioning
confidence: 99%
“…Patch tests have been suggested to be especially useful to diagnose nonimmediate hypersensitivity to anticonvulsants and NSAIDs, but further large studies are needed to evaluate their diagnostic value .…”
Section: Diagnostic Approach To Drug Hypersensitivity In Childrenmentioning
confidence: 99%
“…Some allergological studies, mostly in adults, rarely including children, reported on results of skin tests and provocation tests (17,21,55,57,77,78). A problem in diagnosing macrolide hypersensitivity is that some macrolides are not available in injectable form and hence IDTs are not possible.…”
Section: Macrolidesmentioning
confidence: 99%
“…Sensitivity and specificity for this concentration in IDT have been reported as 75% and 90%, respectively. In a limited number of studies that included few children, all or most of children with suspected macrolide hypersensitivity tolerated oral provocation, and up to only 12% of the reactions were confirmed (17,21,55,60,77,78).…”
Section: Macrolidesmentioning
confidence: 99%